Analisa Kualitas Tebu Menggunakan Metode Hydrolic Press dan Jeffco dengan Dessentegrator - Barokah , Lailatul (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Sugar cane is a type of herbaceous plant which contains a lot of sugar. This study aims to determine the results of% pol (sugarcane purification) and% brix (sugarcane concentration) from sugarcane raw materials if using hydrolic press and jeffco wet dessentegrator methods. The results of this study indicate that% pol and% brix use the unstable hydrolic press and jeffco wet dessegrator method because the sugar cane used is not sugar cane which is usually used in the milling season.